Stoichiometry of cationic nutrients in Phaeozems derived from skarn and Acrisols from other parent materials in lowland forests of Thailand - Baillie, Ian C.; Bunyavejchewin, Sarayudh; Kaewfoo, Manop; Baker, Patrick J.; Hallett, Stephen H. (Elsevier, 2017)
Some soils under tropical forests in western Thailand are derived from skarn complexes of hydrothermally metamorphosed granitic, calcareous and ultramafic rocks. We used data from six large, long-term forest ecological research plots to compare the soils derived from skarn with forest soils derived from granites and sedimentary parent materials elsewhere Thailand. The soils derived from skarn are Vermic Phaeozems and have deep, dark, worm-worked topsoils and bimodal particle size distributions of coarse sand and grit in clay or fine loam matrices. They are eutrophic with respect to both labile and non-labile forms of the mineral nutrients. The soils derived from other parent materials are mostly Acrisols. Analyses of variance for the cationic nutrients taken independently clearly distinguished the Phaeozems from the Acrisols. The two groups are also stoichiometrically distinct with respect to the main cationic nutrients, as depicted graphically by nutrient roses and as quantified as M+:TEB ratios. The cationic stoichiometric proportions also differentiated between the Acrisols on different plots and parent materials; and between the Phaeozems in our study and eutrophic soils in lowland forests elsewhere in the lowland tropics, with the Phaeozems having lower exchangeable Ca and Mg contents but higher exchangeable K. Subsoil cationic stoichiometric profiles appear to derive from parent materials, but those of the topsoil may be modified by selective biotic recycling. Nonetheless, inherited lithogenic stoichiometric ratios are still apparent in our topsoils. The forests on skarn in West Thailand are varied and overlap with those on Acrisols and other soils. This confirms earlier findings that climate and disturbance history have more influence than soils on the regional distribution of forest types in Thailand, although soils can be important at more local scales.
Keywords: Nutrient rose; Vermic; Earthworms; Termites; Phaeozems; Mollisols; Acrisols; Ultisols